Lithium fluoride colour centres-based imaging detectors for proton beam characterization at high doses. (July 2016) - Piccinini, M.; Ampollini, A.; Picardi, L.; Ronsivalle, C.; Bonfigli, F.; Libera, S.; Vincenti, M.A.; Montereali, R.M.
Abstract: Proton beams of 7 MeV energy, produced by a linear accelerator, were used to irradiate LiF crystals and thin films thermally evaporated on glass substrates in the dose range from 10 3 to 4 × 10 6 Gy, inducing the formation of stable photoluminescent colour centres (mainly F2 and F3 + ), emitting in the visible spectral range. Using a conventional fluorescence microscope, the transversal proton beam intensity was mapped by acquiring the photoluminescence image of the irradiated spots. Image analysis allowed measuring the integrated photoluminescence intensity as a function of the irradiation dose: a linear optical response was obtained up to different maximum dose values, after which a quenching was observed, depending on the nature of the samples (crystals or films). The colour centres formation was investigated by optical absorption spectroscopy at room temperature and the Principal Component Analysis was applied to the absorption spectra of irradiated LiF crystals. In samples irradiated at highest doses, it allowed clearly identifying the formation of more complex aggregate defects, which appears strictly related to the observed photoluminescence quenching effect. Highlights: Photoluminescence of colour centres in LiF can be used for 2-D proton beam imaging. Photoluminescence response of colour centres in LiF films is linear over several orders of magnitude of proton dose range. Principal Component Analysis was applied to optical absorption spectra to highlight defect formation with dose in LiF. LiF crystals and thin films are promising for proton beam characterization/dosimetry by photoluminescence at high doses.